SOSIALISASI PENGARSIPAN DIGITAL PADA SEKOLAH SMK NEGERI 3 DEPOK - Nugroho, Feri; Ulfah, Rahmawati; Dewi, Nur Fitri; Salamah, Ummy Gusti; Islami, Agnemas Yusoep; Wijaya, Hadi; Maghfuriyah, Alfi; Hertin, Revita Desi; Ridho, Ali; Udriyah; Rachmawati, Dwi (Jurnal Abdi Insani, 2024)
The use of technology has become a crucial element in various sectors, including in the realm of education. In the scope of education, technology plays an integral role in various aspects of learning and school operations. The focus of technology lies not only in the learning process, but also in the administrative and managerial aspects that underlie the daily life of school organizations. In this context, the use of technology helps achieve educational goals in a more efficient way, expands accessibility, and increases the effectiveness of educational activities. To make data management more organized and make it easier for users to manage documents. The activity method used in community service is qualitative, carried out by organizing teaching to socialize digital archives at SMK Negeri 3 Depok. Various communication techniques such as lectures and discussions are used: lectures for structured exposure, discussions for active participation of participants in discussions and questions and answers. From the results of the socialization of digital archives at SMK Negeri 3 Depok, 14 OTKP grade 12 students were actively involved. Students are invited to get to know various digital archive storage platforms such as g-Drive, spreadsheets, OneDrive, iCloud, and E-Library. From the various aspects discussed in the socialization of digital archives at SMK Negeri 3 Depok, participants have gained a broad understanding of digital archive storage platforms and services such as g-Drive, spreadsheets, OneDrive, iCloud, and E-Library. This introduction provides provisions for participants in managing digital archives, improves their skills in technology, and broadens their understanding of the benefits of digital archives in work. Participants have gained a lot of understanding and know how to organize data using various digital archiving platforms.